Resistive-type VOCs and pollution gases sensor based on SnO2: A review. (February 2022) - Kang, Xiaoying; Deng, Nanping; Yan, Zirui; Pan, Yingwen; Sun, Wei; Zhang, Yaofang
Abstract: The uncontrolled emission of toxic and harmful gases will seriously restrict the sustainable development of social economy system and threaten people's health. Therefore, it is essential to detect and monitor them effectively and quickly. Metal oxide sensor is one of the most common sensors to detect these gases, with high stability, strong selectivity and other characteristics. Among them, tin dioxide (SnO2 ) based sensor has been widely used due to its semiconductor sensor characteristics. This review not only presents the sensing mechanism of SnO2 sensors, but also summarizes and reviews the various methodological used to improve the gas sensing performance of SnO2 based gas sensors, including changing the morphology and structure, doping, and dynamic response and sensor arrays. The composite sensor can significantly improve the sensing performance of the gas sensor against toxic and harmful gases. Finally, possible solutions are proposed for the existing difficulties of SnO2 -based gas sensors. Graphical abstract: Overview of the topics covered in this review. Image 1